Cardiac Output and Cerebral Oxygenation in Term Neonates during Neonatal Transition - Baik-Schneditz, Nariae (Children (Basel), 2021)
The immediate transition from foetus to neonate includes substantial changes, especially concerning the cardiovascular system. Furthermore, the brain is one of the most vulnerable organs to hypoxia during this period. According to current guidelines for postnatal stabilization, the recommended parameters for monitoring are heart rate (HR) and arterial oxygen saturation (SpO(2)). Recently, there is a growing interest in advanced monitoring of the cardio-circulatory system and the brain to get further objective information about the neonate’s condition during the immediate postnatal transition after birth. The aim of the present study was to combine cardiac output (CO) and brain oxygenation monitoring in term neonates after caesarean section in order to analyse the potential influence of CO on cerebral oxygenation during neonatal transition. This was a monocentric, prospective, observational study. For non-invasive cardiac output measurements, the electrical velocimetry (EV) method (Aesculon Monitor, Osypka Medical, CA, USA) was used. The pulse oximeter probe for SpO(2) and HR measurements was placed on the right hand or wrist. The cerebral tissue oxygen index (cTOI) was measured using a NIRO-200NX monitor with the near-infrared spectroscopy (NIRS) transducer on the right frontoparietal head. Monitoring started at minute 1 and was continued until minute 15 after birth. At minutes 5, 10, and 15 after birth, mean CO was calculated from six 10 s periods (with beat-to-beat analysis). During the study period, 99 term neonates were enrolled. Data from neonates with uncomplicated transitions were analysed. CO showed a tendency to decrease until minute 10. During the complete observational period, there was no significant correlation between CO and cTOI. The present study was the first to investigate a possible correlation between CO and cerebral oxygenation in term infants during the immediate neonatal transition. In term infants with uncomplicated neonatal transition after caesarean section, CO did not correlate with cerebral oxygenation.